The Adsorption of Mixed Dyes (Acidic and Basic) on to Hardwood in a Fixed Bed - Yehia H. Magdy (Adsorption Science & Technology, 1996)
The adsorption of mixed dyes, Acid Blue and Basic Red, on to hardwood sawdust has been studied using the fixed bed technique. The influence of various parameters such as bed depth, solution flow rate and dye concentration were studied. The modified bed depth service time (BDST) model has been used to analyze the experimental data. In addition the empty bed residence time (EBRT) technique has been applied to optimize the adsorption process variables for either single or multi-component dyes.